Herbal remedies as a potential alternative therapy for arthritis - Disha Trivedi; Riya Jayapal Roja; Eva Künnemann (Academia Biology)
The use of natural compounds has been significant for human health since centuries. However, only with molecular techniques and cell biology experiments, the function of these interactions can be shown and their therapeutic use in medicine be proven. In this review, we show the pathology of osteoarthritis and rheumatoid arthritis, a disease condition affecting millions of people worldwide and we describe herbal materials that are used for arthritis treatment. In detail, we describe how different plant substances, that is, curcumin and several ingredients of rosehip, can interact with cartilage compounds and reduce the inflammatory reaction by specifically interacting with cellular pathways. Arthritis forms a vicious cycle, where upon overuse of a joint or an autoimmune reaction inflammation and pain occur. These are marked by specific molecular patterns and immunological pathways that lead to chondrolysis and destruction of cartilage. Natural plant substances can influence these pathways and help to break out of the vicious cycle and to find a way for stopping the disease or even to regenerate and heal injured cartilage. In conclusion, rosehip, curcumin and other natural remedies are effective treatments and combinations are possible. Bioavailability of the substances is important and can be increased with specific enhancers. We also discuss that targeting pain only without treating cartilage degeneration can lead to unnoticed further irreparable decay and advice to treat pain and joint health at once. Additionally, regular movement of the joints is necessary for natural compounds to act in the human body and provide wellness.